Exploring the cognitive, hedonic, and emotional dimensions of tourist purchase intentions for ethnic foods: A qualitative inquiry - Ahmad Shakani Abdullah; Ramraini Ali Hassan; Wan Rusni Wan Ismail (RSIS International, 2025)
The purpose of this study is to investigate the effects of cognitive, hedonic, and emotional factors on Sabah’s tourists’ desire to purchase ethnic food. In this study, a combination of cognitive, hedonic as well as emotional drivers is examined in the purchase intentions of tourists in the Sabah region of Malaysia towards ethnic food. Since little is known about these psychological motivators in food tourism, this study follows a simple qualitative investigation in an attempt to draw more details about the behavior of tourists. Five participants (three local tourists of Peninsular Malaysia and two international tourists of China and Korea) took part in the in-depth semi-structured interviews (collected the data). Theme and thematic analysis were done manually to see a pattern and recurring theme. Four overall themes were identified: a sense of unusualness and appeal, food authenticity, and safety, emotional appeal, and the power of social and contextual factors. The findings indicate that visual appeal, cultural stories and emotion connection increases probability of the tourists to sample ethnic foods. The current paper would add to the food tourism literature by providing a conceptual framework, which would combine psychological aspects with the food decision-making. Marketing and tourism agencies practical implication is also discussed.